N-Termini of Fungal CSL Transcription Factors Are Disordered, Enriched in Regulatory Motifs and Inhibit DNA Binding in Fission Yeast - Převorovský, Martin (Public Library of Science, 2011)
BACKGROUND: CSL (CBF1/RBP-Jκ/Suppressor of Hairless/LAG-1) transcription factors are the effector components of the Notch receptor signalling pathway, which is critical for metazoan development. The metazoan CSL proteins (class M) can also function in a Notch-independent manner. Recently, two novel classes of CSL proteins, designated F1 and F2, have been identified in fungi. The role of the fungal CSL proteins is unclear, because the Notch pathway is not present in fungi. In fission yeast, the Cbf11 and Cbf12 CSL paralogs play antagonistic roles in cell adhesion and the coordination of cell and nuclear division. Unusually long N-terminal extensions are typical for fungal and invertebrate CSL family members. In this study, we investigate the functional significance of these extended N-termini of CSL proteins. METHODOLOGY/PRINCIPAL FINDINGS: We identify 15 novel CSL family members from 7 fungal species and conduct bioinformatic analyses of a combined dataset containing 34 fungal and 11 metazoan CSL protein sequences. We show that the long, non-conserved N-terminal tails of fungal CSL proteins are likely disordered and enriched in phosphorylation sites and PEST motifs. In a case study of Cbf12 (class F2), we provide experimental evidence that the protein is proteolytically processed and that the N-terminus inhibits the Cbf12-dependent DNA binding activity in an electrophoretic mobility shift assay. CONCLUSIONS/SIGNIFICANCE: This study provides insight into the characteristics of the long N-terminal tails of fungal CSL proteins that may be crucial for controlling DNA-binding and CSL function. We propose that the regulation of DNA binding by Cbf12 via its N-terminal region represents an important means by which fission yeast strikes a balance between the class F1 and class F2 paralog activities. This mode of regulation might be shared with other CSL-positive fungi, some of which are relevant to human disease and biotechnology.